2023
DOI: 10.1136/jnis-2023-020582
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion for the treatment of intracranial bifurcation aneurysms: a systematic review and meta-analysis

Abstract: BackgroundFlow diversion (FD: flow diversion, flow diverter) is an endovascular treatment for many intracranial aneurysm types; however, limited reports have explored the use of FDs in bifurcation aneurysm management. We analyzed the safety and efficacy of FD for the management of intracranial bifurcation aneurysms.MethodsA systematic review identified original research articles that used FD for treating intracranial bifurcation aneurysms. Articles with >4 patients that reported outcomes on the use of FDs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This relatively high rate of ischemic complications has also been described in previous studies involving FDS treatment of MCA bifurcation aneurysms. 20 A recent study demonstrated a significant delay in the MR brain perfusion values was detected in the vascularized territory of a jailed arterial branch following flow diversion when compared with the contralateral MCA territory. 21 Although these changes in arterial flow were rarely accompanied by clinical findings in the aforementioned study, 21 further interpretation was limited by its modest sample size of 18 patients.…”
Section: Discussionmentioning
confidence: 98%
“…This relatively high rate of ischemic complications has also been described in previous studies involving FDS treatment of MCA bifurcation aneurysms. 20 A recent study demonstrated a significant delay in the MR brain perfusion values was detected in the vascularized territory of a jailed arterial branch following flow diversion when compared with the contralateral MCA territory. 21 Although these changes in arterial flow were rarely accompanied by clinical findings in the aforementioned study, 21 further interpretation was limited by its modest sample size of 18 patients.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy in bleeding rates was attributed to the administration of tirofiban, facilitating a prompt restoration of platelet function upon discontinuation. A recent meta-analysis investigating the utilization of flow diversion-assisted embolization for intracranial bifurcation aneurysms reported TEs and HEs incidences of approximately 16 and 4%, respectively ( 29 ). In the present study, the incidence of TEs was notably lower compared to the meta-analytic findings, while the incidence of HEs was marginally higher; however, it is critical to note that no severe bleeding events were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The WEB device is designed for wide-necked bifurcation aneurysms and is typically used at four typical locations: the MCA bifurcation, AcomA, basilar apex and ICA apex ( 12 , 50 ). After deployment in the aneurysm sac, the device provides immediate flow disruption, leading to aneurysm thrombosis and endothelialization across the aneurysm neck over time.…”
Section: Various Evt Techniquesmentioning
confidence: 99%
“…Ruptured or daughter-sac/multilobed, large or giant, growing ICA bifurcation region aneurysms may need treatment, including open surgery and endovascular treatment (EVT) (7)(8)(9)(10). Currently, EVT, including traditional coiling, flow diverter (FD) and Woven EndoBridge device (WEB) (MicroVention, Tustin, California, United States) deployment, has been used for the treatment of ICA bifurcation region aneurysms (11,12). However, EVT is challenging due to the unfavorable morphologic features of ICA bifurcation aneurysms.…”
Section: Introductionmentioning
confidence: 99%